Creative learning : - Lucas, Robert W. (Pfeiffer,J. Wiley & Sons, 2007)
Creative Learning is written by master trainer Bob Lucas, and offers a treasure trove of innovative and highly effective activities to simulate learning. The activities are tailor-made for trainers, presenters, and educators, and can be put to use in virtually any type of learning environment. Each activity offers a different approach to learning, but all are designed using a brain-based-learning approach that is proven to mentally or physically engage learners and enhance their learning experience.